Анализ статического и ударного деформирования керамического контейнера для радиоактивных отходов - Саенко, С. Ю.; Морачковский, Олег Константинович; Лавинский, Денис Владимирович; Соболь, Владимир Николаевич (НТУ "ХПИ", 2010)
The static and impact deformation analysis of the ceramic container for transporting and burial of radioactive materials have been done. The strength and tightness estimations taking to account normative standards for designing of such objects are given. Such estimations have been given for container, which unlike to existing ones, made from ceramic type ZrO2 [1]. The comprehensive results of analysis, obtained on the basis of finite elements method by using COSMOS/ANSYS and KIDYM software, are presented
Keywords: радиационное загрязнение; радиоактивные материалы; программные комплексы COSMOS/ANSYS; программный комплекс КИДИМ